The profiling of al-Roznah in Omani interior design: from cultural identity to contemporary loss and reinterpretation - Hamdan, Hadifi Wafaa Awadh; Awang, Arita Hanim (IIUM Press, 2025)
This study examines the evolution of AL-Roznah, a traditional architectural element in Omani’s interior design. It has multifunctional elements, blending aesthetics and practicality. The research further explored the cultural significance, the functional role and the decline of AL-Roznah in contemporary interiors. A qualitative method was employed, and semi-structured interviews were conducted. The fieldwork was conducted in four (4) historical neighbourhoods in Al-Dakhiliyah Governorate, documenting variations in AL-Roznah’s design, materials, and uses. The findings have shown the shifting role from a symbol of Omani cultural identity to primarily decorative features due to several factors. Thus, the article highlighted the efforts for AL-Roznah's restoration of traditional values into contemporary interior design for future generations.